Long-term influence of concussion on cardio-autonomic function in adolescent hockey players - Memmini, A. K.; La Fountaine, M. F.; Broglio, S. F.; Moore, R. D. (Journal of Athletic Training, 2021)
Context: Concussion may negatively influence cardiovascular function and the autonomic nervous system, defined by alteration in heart rate variability (HRV). Differences in HRV most commonly emerge during a physical challenge, such as the final steps of the return-to-sport progression. Objective: To assess the effect of concussion history on aspects of cardio-autonomic function during recovery from a bout of submaximal exercise in adolescent male hockey athletes. Design: Case-control study. Setting: Research laboratory. Patients or Other Participants: Thirty-three male athletes participating in Midget-AAA hockey were divided into those with (n = 15; age = 16 ± 1 years, height = 1.78 ± 0.06 m, mass = 73.9 ± 7.4 kg, 10.5 ± 1.6 years of sport experience, 25.2 ± 18.3 months since last injury) or without (n = 18; age = 16 ± 1 years, height = 1.78 ± 0.05 m, mass = 74.8 ± 7.6 kg, 10.6 ± 1.9 years of sport experience) a concussion history. Those with a concussion history were binned on total count: 1 concussion or 2 or more concussions. Intervention(s): All athletes underwent 5 minutes of resting HRV assessment, followed by 20 minutes of aerobic exercise at 60% to 70% of their maximal target heart rate and a 9-minute, postexercise HRV assessment. Main Outcome Measure(s): Heart rate variability measures of mean NN interval, root mean square of successive differences, and standard deviation of NN interval (SDNN). Results: Group demographic characteristics were not different. When the control and concussed groups were compared, group and time main effects for heart rate recovery, root mean square of successive differences, and SDNN (P values < .01), and an interaction effect for SDNN (P < .05) were demonstrated. Recovery trends for each group indicated that a history of 2 or more concussions may negatively affect cardio-autonomic recovery postexercise. Conclusions: Our findings suggest that those with more than 1 previous concussion may be associated with a greater risk for long-term dysautonomia. Future use of HRV may provide clinicians with objective guidelines for concussion-management and safe return-to-participation protocols.